Evaluation of in vitro bioactivity of Melaleuca cajuputi powell essential oil against Aedes aegypti (L.) and Aedes albopictus (Skuse) - Azlinda Abu Bakar,; Hamdan Ahmad,; Sallehudin Sulaiman,; Baharudin Omar,; Rasadah Mat Ali, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The aim of this study was to evaluate the in vitro activity of Melaleuca cajuputi essential oil leaf extract against Aedes aegypti and Aedes albopictus. The essential oil of the M. cajuputi was obtained via steam hydro-distillation and analyzed by GC-MS for the chemical constituents. GC-MS analysis showed that the essential oil of M. cajuputi contained 13 compounds with two major chemical constituents, 2-propenoic acid (29.55%) and caryophyllene (20.04%). Adulticidal and larvicidal bioassay was evaluated following WHO guidelines. Larvicidal bioassays were conducted with the 10, 50, 80, 100, and 120 mg/L M. cajuputi essential oil against late 3rd instar of Ae. aegypti and Ae. albopictus which give LC50 120.99 mg/L and 222.58 mg/L, respectively. Adult mortality was observed after 24 h with the LC50 of 0.029 mg/cm2 for Ae. aegypti and 0.028 mg/cm2 for Ae. albopictus. In adulticidal bioassay, M. cajuputi essential oils showed effective results at 0.04 mg/cm2 concentrations, with values for KT50 of 77.71 min for Ae. aegypti and 69.49 min for Ae. albopictus. M. cajuputi essential oils exhibited moderate toxicity effects against the larva and adults of Aedes species and may be used as an alternative to chemical insecticide.